Analyse rétrospective de l’impact d’événements de la vie scolaire sur la construction de l’identité - Lecacheur, Mireille; Massonnat, Jean (Canadian Journal of Counselling and Psychotherapy, 1993)
Based on self-analysis and the evocation by 225 adult subjects of the impact of salient school events during adolescence, the authors studied the effects of contrasted life events on person construction by examining the memories subjects have of such events. The events concerned obstacles or difficulties which were/were not overcome (OS and ONS respectively). A comparative approach was used to provide evidence of the specific effects of OS and ONS on the various dimensions of identity. The discussion raises the question of the validity of retrospective analysis and the meaning of events analyzed as such.